2004
DOI: 10.1590/s0100-879x2004001000014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of centrally acting antihypertensive drugs on the microcirculation of spontaneously hypertensive rats

Abstract: We investigated the acute effects of centrally acting antihypertensive drugs on the microcirculation of pentobarbital-anesthetized spontaneously hypertensive rats (SHR). The effects of the sympatho-inhibitory agents clonidine and rilmenidine, known to activate both α 2 -adrenoceptors and nonadrenergic I 1 -imidazoline binding sites (I 1 BS) in the central nervous system, were compared to those of dicyclopropylmethyl-(4,5-dimethyl-4,5-dihydro-3H-pyrrol-2-yl)-amine hydrochloride (LNP 509), which selectively bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…As discussed above, the concomitantly enhanced A 2A R signaling in the RVLM of ABD rats (Nassar and Abdel-Rahman, 2008) makes it difficult to discern the role of A 1 R signaling in clonidine-evoked hypotension. Although no study has directly investigated the role for central A 1 R signaling in clonidine-evoked hypotension, our conclusion is strengthened by the findings that in the SHR, which exhibits attenuated pressor responses to intra-nucleus tractus solitarius adenosine (Abdel-Rahman and Tao, 1996), clonidine lowers blood pressure (Jastrzebski et al, 1995;Estato et al, 2004). It must be noted that the pressor response elicited by adenosine reflects A 1 R signaling (Scislo and O'Leary, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…As discussed above, the concomitantly enhanced A 2A R signaling in the RVLM of ABD rats (Nassar and Abdel-Rahman, 2008) makes it difficult to discern the role of A 1 R signaling in clonidine-evoked hypotension. Although no study has directly investigated the role for central A 1 R signaling in clonidine-evoked hypotension, our conclusion is strengthened by the findings that in the SHR, which exhibits attenuated pressor responses to intra-nucleus tractus solitarius adenosine (Abdel-Rahman and Tao, 1996), clonidine lowers blood pressure (Jastrzebski et al, 1995;Estato et al, 2004). It must be noted that the pressor response elicited by adenosine reflects A 1 R signaling (Scislo and O'Leary, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…Whereas clonidine-evoked hypotension manifests in hypertensive rats, conscious or anesthetized (Jastrzebski et al, 1995;Estato et al, 2004), it only manifests in anesthetized, but not conscious, normotensive rats (El-Mas et al, 1994;Yang et al, 2005). Reported studies including ours have shown that partial or complete baroreceptor denervation unmasks the hypotensive effect of clonidine in conscious normotensive rats (Abdel-Rahman, 1992;El-Mas and AbdelRahman, 1997;Medvedev et al, 1998).…”
mentioning
confidence: 71%
“…Although, clonidine is classified by Bousquet as an agonist at imidazoline-binding sites, it is still considered a mixed I 1 /␣ 2A agonist Estato et al, 2004). Therefore, it was difficult to ascertain the receptor, I 1 or ␣ 2A , whose activation triggers central adenosine signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional studies demonstrated that administration of harmane into rat brain RVLM elicited a hypotensive response which was also observed with I 1 -BS ligands clonidine, rilmenidine, moxonidine and LNP 509 [101,102]. Furthermore, the central antihypertensive action of harmane and clonidine was reversed by the mixed α 2 -AR/I 1 -BS antagonist efaroxan.…”
Section: Harmane -The Endogenous Ligand At Imidazoline Binding Sites?mentioning
confidence: 84%